Cross Saturation Inductance Analysis of a Permanent Magnet Synchronous Motor - Ergene, Lale T.; İmeryüz, Murat; Ekin, Cihad (Balkan Journal of Electrical & Computer Engineering (BAJECE), 2018)
This paper presents the cross saturation effect on a specially designed spoke type permanent magnet synchronous motor (PMSM) for the sensorless vector control. The cross saturation effect becomes very important where the sensorless control algorithm is used. Accurate flux linkage modeling is required to obtain a satisfactory position estimation and eventually minimum induced torque error. The magnetic saturation is the most impacting parameters affecting the position error. Since the Ld and Lq inductance difference is generally less than 5% in the spoke type PMSM, the accurate estimation of the cross saturation is critical for the sensorless vector control.  In this paper, the designed PMSM has the Ld and Lq difference in 15% level even for the overload capacity. So it is even possible to operate the motor in the transient modes with the overload capacity by estimating right cross saturation effect with certain time limits. The mapping of the inductances and efficiency are obtained by using Finite element method and presented in the paper. Some experimental results are also given such as efficiency and power-speed variation at the constant torque.
Keywords: Engineering; Permanent magnet synchronous motor; finite element method; cross saturation effect; d-q inductances; sensorless vector control; Mühendislik